Isolamento de Streptococcus agalactiae em diferentes órgãos de tilápias do nilo (Oreochromis niloticus) criadas em tanques-rede - Marcusso, Paulo Fernandes [UNESP]; Eto, Silas Fernandes [UNESP]; Claudiano, Gustavo da Silva [UNESP]; Vieira, Flávia Campos Freitas [UNESP]; Salvador, Rogério; Moraes, Julieta Rodini Engrácia de [UNESP]; Moraes, Flávio Ruas de [UNESP] (Univ Federal Uberlandia, 2015)
Streptococcosis is one of the major causes of mortality in tilapia's creation in Brazil, inducing great economic losses. As soon, the study objectived to determinate the frequency of isolation and identification the Streptococcus agalactiae in organs different of Oreochromis niloticus naturally infected, derived from eight fish farms in the northern region of the state of Parana, that presented clinical signs characteristics of streptococcal disease. However, blood samples and fragments (kidney, liver, spleen, heart and brain) were collected. These all samples were plated on solid medium of brain and heart infusion (BHI) added 5% ovine blood and incubated at 29 degrees C for 7 days in aerophilic conditions. Behind, the bacterial growth and from the macro and microscopic features, colonies compatibles with Streptococcus sp. gender, were selected. The species were identified by PCR reaction and confirmed by sequencing of 16S rDNA gene. The results exhibited that in tilapia of Nile infected with S. agalactiae the isolation is more common in brain, kidney and liver in descending order.

A estreptococose é uma das principais causas de mortalidade na criação de tilápias no Brasil, causando grandes perdas econômicas. Assim, o estudo objetivou determinar a frequência de isolamento e identificação por PCR de Streptococcus agalactiae em diferentes órgãos de tilápias do Nilo (Oreochromis niloticus) naturalmente infectadas, oriundas de oito pisciculturas da região norte do estado do Paraná que apresentavam sinais clínicos característicos de infecção estreptocócica. Para tanto, coletaram-se amostras de sangue e fragmentos de rim, fígado, baço, coração e encéfalo. Essas foram semeadas em meio ágar infusão de cérebro e coração (BHI) adicionado 5% de sangue de ovino e incubados à 29ºC, durante 7 dias em aerofília. Após o crescimento bacteriano e a partir das características macro e microscópicas, foram selecionadas colônias compatíveis com as do gênero Streptococcus sp.. As espécies foram identificadas através de PCR e confirmadas por meio do sequenciamento do gene 16S rDNA. Os resultados demonstraram que em tilápias do Nilo infectadas com S. agalactiae, o isolamento é mais frequente em encéfalo, rim e fígado em ordem decrescente.
Isolation of Streptococcus agalactiae in different organs of nile tilapia (Oreochromis niloticus) reared in net cages
Keywords: Streptococcosis; Oreochromis niloticus; Bacteriosis; Teleosts; Estreptococose; Oreochromis niloticus; Bacteriose; Teleósteos